Acceptance of shari?ah-compliant precious metal-backed cryptocurrency as an alternative currency: an empirical validation of adoption of innovation theory - Ajouz, Mousa; Abdullah, Adam; Kassim, Salina (Wiley-Liss Inc., 2019)
In the crypto world, there is a proverbial (and literal) gold rush now occurring. Currently, more than 37 gold-backed cryptocurrency companies have now emerged. Interestingly, some of them also claim to be Sharīʿah-compliant. Introducing precious metal-backed cryptocurrencies is perceived to be an innovation among global payment systems, hampered in part by lack of supporting empirical evidence. Therefore, this research investigates potential users' tendency to adopt a Sharīʿah-compliant precious metal-backed cryptocurrency. As such, this study adopts an extended adoption model, which consists of eight factors. Partial least squares structural equation modeling (PLS-SEM) analysis was conducted on data elicited from economic active residents in Klang Valley from questionnaires. Overall, it was found six out of the eight constructs specified to influence the adoption of precious metal-backed cryptocurrency were statistically significant where 54.5% of the variation in adoption of PMBC can be explained by the structure model provided by this research. It was also found 63.55% of the respondents are willing to adopt precious metal-backed cryptocurrency in their future transactions.